1996
DOI: 10.1007/s002469900076
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Pulmonary Hypertension Due to Disseminated Fibromuscular Dysplasia

Abstract: We present two patients with thromboembolic pulmonary hypertension associated with unusual complications probably caused by disseminated fibromuscular dysplasia (FMD) or FMD-like vascular lesions. Intimal fibroplasia, which is typical of the vascular lesions associated with FMD, was observed in both patients. The presence of such intimal lesions suggests that there was a systemic factor that caused the formation of recurrent thrombi in the systemic vessels in these patients. These cases are the first ones repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The histopathological pulmonary vessel abnormalities were compatible with intimal FMD. We found only two cases with moyamoya and primary pulmonary hypertension in the English literature [4,7]. Fukuhara et al have already suggested that a systemic angiopathy, such as intimal FMD, could be the cause of the moyamoya syndrome as well as the primary pulmonary hypertension in their patient [4].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The histopathological pulmonary vessel abnormalities were compatible with intimal FMD. We found only two cases with moyamoya and primary pulmonary hypertension in the English literature [4,7]. Fukuhara et al have already suggested that a systemic angiopathy, such as intimal FMD, could be the cause of the moyamoya syndrome as well as the primary pulmonary hypertension in their patient [4].…”
Section: Discussionmentioning
confidence: 63%
“…Ikeda has studied the pathological features of extracranial arteries in eleven patients with moyamoya disease that had no symptoms of extracranial vascular disease [6]. The intima-tomedia ratio of pulmonary, renal, and pancreatic arteries was significantly increased as compared to control subjects, suggesting that the presence of both systemic and local factors can cause the Fibromuscular dysplasia is a systemic vascular disorder that has been suggested to be the cause of moyamoya syndrome and associated extracranial arterial disease [4,8,9]. The progressive stenosis of the carotid arteries in FMD may lead to the angiographical appearance of moyamoya [2].…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic findings include vascular wall fibroplasia, disruption of the elastic membrane and formation of small saccular aneurysms [10]. Medial fibroplasia is the most common dysplastic lesion, but intimal dysplasia occurs in approximately 10% of FMD and is more often seen in children [11]. The development of arterial aneurysms and vascular lesions mimicking FMD in a child with IM is uncommon and intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…1 A few cases of the disease have recently been reported with extracranial arterial lesions, suggesting a diffuse arteriopathy as the underlying cause. [2][3][4][5][6] We report here the details of a child presenting with the disease in the setting of a multisystemic arteriopathy, including renal and pulmonary arterial stenoses. To our knowledge, an association of these three conditions has not thus far been reported.…”
mentioning
confidence: 99%